Molecular dynamics simulation of biomolecular - synthetic surface interactions - Wong, Lynn Hee (2008)
The surface interaction between the hepatic asialoglycoprotein receptor (ASGPR) and collagen molecules using molecular dynamics simulation. The interaction energies of the receptor-collagen and their complex with water were calculated using a Hyperchem molecular mechanics model.